2017
DOI: 10.1108/rpj-09-2015-0122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of build orientation on the mechanical reliability of 3D printed ABS

Abstract: Purpose Increasing use of 3D printing techniques to manufacture consumer products and open-source designs raises the question of “What is the mechanical reliability of 3D printed parts?” Therefore, the purpose of this paper is to investigate the impacts of build orientation on the mechanical reliability of acrylonitrile butadiene styrene (ABS) produced using 3D printing. Design/methodology/approach Tensile tests on ABS specimens were performed with and without a hole in the center, which were produced by fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 41 publications
5
82
1
5
Order By: Relevance
“…The reliability of the 80 % infill seems to be correlated to the large distribution of density, as shown in Figure 2b. In our previous study, we reported similar and values for short carbon-fiber composite samples at the same infill parameter settings [18,37,38]. The strain at fracture m value was much lower than previous carbon-fiber composite results.…”
Section: Resultssupporting
confidence: 47%
See 3 more Smart Citations
“…The reliability of the 80 % infill seems to be correlated to the large distribution of density, as shown in Figure 2b. In our previous study, we reported similar and values for short carbon-fiber composite samples at the same infill parameter settings [18,37,38]. The strain at fracture m value was much lower than previous carbon-fiber composite results.…”
Section: Resultssupporting
confidence: 47%
“…Recent work has shown that FDM produces parts with lower mechanical reliability than their subtractive manufactured counterparts [18]. These part-to-part variations can pose harm to consumers using FDM for load-bearing applications.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This presents a discontinuity in the design process, since manufacturing parameters are applied after strength predictions are made, implying that stress analyses are unreliable unless the numerous parameters applied in the slicing and toolpath generation phase have been considered upstream in the stress-analysis phase [17]. The gap in the process chain between stress analysis and the assignment of manufacturing parameters is a factor that significantly limits the reliability of (particularly) FDM 3D printing methods for the production of end-use components [18]. A method of AM where toolpaths are generated directly based on stress analysis could, to a large extent, remove this discontinuity.…”
Section: Am Process Chainmentioning
confidence: 99%